An experience in mixing cognitive and affective teaching approaches in a CS1 course - Josko, João Marcelo Borovina (Anais do Workshop sobre Educação em Computação (WEI); 2021: Anais do XXIX Workshop sobre Educação em Computação, 2021)
Learning computer programming involves overcoming different obstacles to mature technical, cognitive, and social skills. The literature presents a variety of teaching approaches to engage students in learning how to program. However, there is a lack of works that combine different teaching methods from cognitive and affective dimensions or consider the latter dimension in face-to-face classes consistently. This work presents our experience mixing pair programming, formative feedback, aspects of the affective dimension, and creative programming problems. The preliminary results analysis of three groups (82 students) reveals the contribution of our approach to the pass and fail rates (P = 0.0367 and 0.0329, respectively) corroborated by students’ feedback.